HUMAN THOUGHT PROCESS ON HOTEL ADVERTISEMENTS:: A COGNITIVE LINGUISTICS STUDY - Lee, Cakra; Sukarsih, Ni Nyoman Tri; Wardhana, I Gede Neil Prajamukti (LPPM Universitas Dhyana Pura, 2024)
Conceptual Blending (CB) is a framework within Cognitive Linguistics to create meaning construction that determines brain cognitive functions upon reading hotel advertisements which the study aimed to illustrate and elaborate. The study utilized advancement theory of CB by applying intertextuality concept to create multiple meanings done from prior studies. The study also utilized qualitative method to analyze a poster from ANA Intercontinental Manza Beach Resort through applying non-participant observation, purposive sampling, and triangulation theory methods. To analyze the data, the concepts of data collection, data condensation, data display and data conclusion were used. The study found that the processes of composition, completion, and elaboration within blended space of CB built the meaning construction within human brain. Composition stage created arrays of features from composing features within input spaces that build up new concepts within completion stage. The completion stage then created new concepts based on cultural knowledge combining all the features composed within composition process and the meanings were broaden by elaboration stage which cleared out what the new concepts actually meant for. These processes created the emergent structure which carries novelty meanings from the analysis. In this stage, the meaning has been completely concluded from all the elaborated meaning happening on prior stages.